Entry Conditions and the Transition from Tertiary Education to Employment: A Cross-Country Perspective - John Moffat; Duncan H.W. Roth (Institute of Labor Economics (IZA), 2024)
This paper uses monthly data on tertiary education graduates in 19 European countries covering 2004-2017 to assess the short-run effects of entry conditions on the transition into employment. Using an instrumental variables approach, a one percentage point increase in the unemployment rate is found to reduce the hazard rate of transitioning from unemployment into employment by 6%. The effect is stronger in southern European countries and, within this group, is almost entirely due to negative effects on females.
Keywords: J64; J11; J23; 330; entry conditions; tertiary education graduates; transition to employment; proportional hazards model; residual inclusion